3分之1X +5分之1X + 6分之1X + 148 = X
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 06:30:47
3分之1X+5分之1X+6分之1X+148=X3分之1X+5分之1X+6分之1X+148=X3分之1X+5分之1X+6分之1X+148=Xx/3+x/5+x/6+148=xx-x/3-x/5-x/6=
3分之1X +5分之1X + 6分之1X + 148 = X
3分之1X +5分之1X + 6分之1X + 148 = X
3分之1X +5分之1X + 6分之1X + 148 = X
x/3+x/5+x/6+148=x
x-x/3-x/5-x/6=148
x-10x/30-6x/30-5x/30=148
9x/30=148
x=1480/3
=
x-2-x分之3 分之 1+x分之6 +x^2分之5
3分之x*6分之X-1
解方程;3分之x+x-1分之6=x(x-1)分之x+5
3分之1X +5分之1X + 6分之1X + 148 = X
x-3分之x-x的平方-3x分之x+6+x分之1
2分之1x(6分之5-3分之2)
解不等式组 5分之3x-7<2分之x-2 4分之x-12分之2x-1≥6分之1-3分之x
5分之3x一7>=2分之x-2,4分之x一12分之2x一1>6分之1一3分之x
x+1分之2x=1 x-2分之x-x^2-4分之1=1 x+3分之5=x分之2 x-2分之6=x+3分之x -1
3分之1X+6分之5X=1.4
解方程x-1分之6 +x分之1 =x^-x分之x+5
6分之x-2=x分之x+3-1
4分之x+3=x-5分之x-1
4分之x+3=x-5分之x-1
(x+2)分之(x+1)-(x+7)分之1=(x+3)分之(x+2)-(x+6)分之1
2分之X+1-6分之X-3等于3分之5X+1+1
二分之x+1-6分之5+x=3-3分之x-1的解,
2分之1x减3分之1x等于6分之5 求x